Multiple Family Members With Delayed Cord Separtion and Combined Immunodeficiency With Novel Mutation in IKBKB - Alsum, Zobaida; AlZahrani, Mofareh S.; Al-Mousa, Hamoud; Alkhamis, Nouf; Alsalemi, Abdulkareem A.; Shamseldin, Hanan E.; Alkuraya, Fowzan S.; Alangari, Abdullah A. (Frontiers in Pediatrics, 2020)
Background: Inhibitor of Kappa Kinase 2 (IKK2) deficiency is a recently described combined immunodeficiency. It undermines the NF-κB activation pathway. Methods: The clinical and immunological data of four patients diagnosed with combined immunodeficiency (CID) from two related Saudi families were collected. Autozygosity mapping of all available members and whole exome sequencing of the index case were performed to define the genetic etiology. Results: The patients had early onset (2-4months of age) severe infections caused by viruses, bacteria, mycobacteria and fungi. They all had hypogammaglobinemia and low absolute lymphocyte count. Their lymphocytes fail to respond to PHA mitogen stimulation. A novel homozygous nonsense mutation in IKBKB gene, c.850C>T (p. Arg284*) was identified in the index patient and segregated with the disease in the rest of the family. He underwent hematopoietic stem cell transplantation (HSCT) from a fully matched sibling with no conditioning. The other three patients succumbed to their disease. Interestingly, all patients had delayed umbilical cord separation. Conclusion: IKK2 deficiency causes combined immunodeficiency (CID) with high mortality. Immune reconstitution with HSCT should be considered as early as possible. Delayed umbilical cord separation in CID patients may be a clue to IKK2 deficiency.